Two new Navicula species (Bacillariophyceae) from Western Europe - Beauger, Aude; Voldoire, Olivier; Mertens, Adrienne; Le Cohu, René; van De Vijver, Bart (Phytotaxa, 2015)
During a survey of some springs in the French Central Massif, a new Navicula species (Bacillariophyceae) was found: Navicula sanctamargaritae Beauger sp. nov. A second new Navicula species was observed during a routine biomonitoring project in Flanders: Navicula flandriae Van de Vijver & A.Mertens sp. nov.. The new species are formally described using light and scanning electron microscopy. Both species present a unique set of morphological characters including the structure of the central raphe endings, the striation pattern, the valve dimensions and outline, which allows their separation from similar Navicula taxa such as N. korzeniewskii, N. recens or N. cincta. The ecological preferences of each species are briefly discussed.